(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2020)
This study aims to explore the different reasons that influence people’s decision on responses to early warning. A questionnaire survey, key informant interviews and focus group discussion have been applied to obtain data from the study area for this study. The research reveals that jerry-built roads, fear of theft, disbelief and mistrust about warnings, lack of awareness about hazards and the poor state of the cyclone shelters are the main reason for nonevacuation during cyclones. Besides, past experiences of warning failures, superstitious religious beliefs, fatalism, safety issues for women also worked to influence people’s decision to leave their houses during the warning periods. This study calls the attention of the disaster planners at these crucial findings for taking an immediate step to improve the conditions and save lives in future cyclones. It is highly dangerous to stay at the vulnerable houses during cyclones. The practical implementation of a good disaster preparation plan can be futile if inhabitants are no-responsive to the warning. This study recommends improvement of infrastructures, proper maintenance and construction of shelters, improved security at evacuated houses and the shelters alongside the awareness programs for the inhabitants of the vulnerable locations. It is expected that these interventions will increase the efficiency of the cyclone preparedness plan for future cyclones in Bangladesh. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 8(1), 2019, P 53-60